1981
DOI: 10.2172/6470804
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Dissociated Methanol as an Automotive Fuel: System Performance

Abstract: This report was prepared as an account of work sponsored by the United States Government. Neither the United States nor the United States Department of Energy, nor any of their employees, nor any of their contractors, subcontractors, or their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness or usefulness of any information, apparatus, product or process disclosed, or represents that its use would not infringe privately owned righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…7 The endothermic decomposition of methanol (eq 1) has been demonstrated to produce H 2 -rich syngas as an engine fuel. 8,9 The decomposition products of methanol enable an SI engine to run with an increased compression ratio (14:1), increasing the thermal efficiency. 10 Several patents for generating hydrogen-rich syngas out of methanol to combust the syngas in an automotive engine have been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The endothermic decomposition of methanol (eq 1) has been demonstrated to produce H 2 -rich syngas as an engine fuel. 8,9 The decomposition products of methanol enable an SI engine to run with an increased compression ratio (14:1), increasing the thermal efficiency. 10 Several patents for generating hydrogen-rich syngas out of methanol to combust the syngas in an automotive engine have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Besides steam reforming, methanol can also be decomposed to syngas for use as a motor fuel in order to reduce automobile emissions . The endothermic decomposition of methanol (eq ) has been demonstrated to produce H 2 -rich syngas as an engine fuel. , The decomposition products of methanol enable an SI engine to run with an increased compression ratio (14:1), increasing the thermal efficiency . Several patents for generating hydrogen-rich syngas out of methanol to combust the syngas in an automotive engine have been published. , CH 3 OH CO + 2 normalH 2 goodbreak0em1em⁣ normalΔ H normalr1 ° = 90.36 nobreak0em0.25em⁡ kJ/mol …”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using partially decomposed methanol as a cold start fuel for spark-ignition engines was verified theoretically and experimentally Sjostrom, 1986 and1988a). Finegold et al (1980 and1984) demonstrated the possibilities of utilizing decomposed methanol in a mobile unit. The design, construction and testing of the reactor was done by Voecks et at.…”
Section: Introductionmentioning
confidence: 99%